Chapter Action men: martial fashions in Florence, 1530-1630 - Currie, Elizabeth (Datini Studies in Economic History, 2022)
This chapter analyses the influence of contemporary ideals of valour, physical strength, and martial skill on male court fashions. It outlines the various channels that enabled the propagation of martial styles and begins by examining the close relationship between inner valour and outward display, highlighting the meanings ascribed to the words “bravo” and “bravura” in sixteenth-and seventeenth-century Italian texts and imagery. Florentine courtiers were surrounded by idealised representations and performances of warfare, including mock battles with lavish costumes that were a key feature of Medici propaganda. Soldiers and mercenaries were themselves frequently characterised as fashion setters, associated with gaudy colours, flamboyance, and ornate decorations considered inappropriate male attire in many civic contexts. The chapter proceeds to focus on three key aspects of male dress connected with military might and physical strength: leather upper garments, frogged fastenings on cloaks and gowns, and adherent, short trunk hose. Consumer demand for these styles and their cultural meanings are traced through contemporary literature, visual sources, and archival records.